Buzz pollination in saxofridericia (Poales: Rapateaceae): The case of S. brasiliensis and Euglossini bees [Polinização por vibração em Saxofridericia (Poales: Rapateaceae): O caso de S. brasiliensis e abelhas Euglossini] - Krahl, Amauri Herbert; Zidko, Alexsandro; Corrêa, Marcos Melo; Webber, Antonio Carlos (Rodriguesia, 2020)
The reproductive biology of Saxofridericia brasiliensis species a recently described species, was observed in an area of periodically flooded (“Campina”) in the Amazon region. During the flowering period, inflorescences were bagged to identify if the species could form fruits through spontaneous self-pollination. The flowers presents trichomes at the base of the petals that stained by neutral red. The main pollinators were females of nine species of Euglossa, which collect pollen by vibrating the anthers. However, new studies are needed to fully understand the reproductive strategies in the family, as the pollination by hummingbirds was reported in the tribe Schoenocephalieae, due to the presence of nectaries. © 2020 Instituto de Pesquisas Jardim Botanico do Rio de Janeiro. All rights reserved.
Keywords: Augochloropsis; Buzz pollination; Euglossa; Melittophily; Trichomes